Finite Math and Applied Calculus (6th Edition)

Published by Brooks Cole
ISBN 10: 1133607705
ISBN 13: 978-1-13360-770-0

Chapter 0 - Section 0.3 - Multiplying and Factoring Algebraic Expressions - Exercises - Page 21: 36


$y=-2$ or $y=-4$

Work Step by Step

$y^{2}+6y+8$ =$y^{2}+2y+4y+8$ =$y(y+2)+4(y+2)$ = $(y+2) (y+4) = 0$ $y=-2$ or $y=-4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.